Influence of the Molar Ratio of Co and V in Bimetallic Oxides on Their Pseudocapacitive Properties - Quispe Garrido, Lady V. (2022)
Bimetallic oxides have significant attraction as supercapacitor electrode materials due to their highly reversible redox processes, which are commonly associated with their surface chemistry and morphological features. Here, we report the synthesis, characterization, and electrochemical evaluation of bimetallic oxides with different molar compositions of Co and V (Co0.6V0.4, Co0.64V0.36, Co0.68V0.32, and Co0.7V0.3 denoted as S1, S2, S3, and S4 samples, respectively). The materials were synthesized by a modified solvothermal method using glycerol as a stabilizing agent, characterized by X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, scanning electron microscopy–energy-dispersive X-ray spectroscopy, X-ray fluorescence spectroscopy, N2 adsorption isotherms, cyclic voltammetry, and galvanostatic charged/discharged in a three-electrode cell. The role of the CoV oxide compositions on the pseudocapacitive properties was studied through the analysis of the energy storage mechanism following the power law and Dunn’s methodology to obtain the b values. An important finding of this work is that CoV oxides exhibited electrochemical characteristics of a pseudocapacitive electrode material even though the charge storage occurs in bulk. This behavior is consistent with the pseudocapacitance generated by redox processes, showing b values of 0.67, 0.53, 0.75, and 0.84, with a capacitive current contribution of 74, 74, 63, and 70% analyzed at a scan rate of 1 mV s–1, for S4, S3, S2, and S1 samples, respectively. Co0.7V0.3 (S4) oxide presented the highest specific capacitance of 299 F g–1 at 0.5 A g–1 with a Coulombic efficiency of 93% tested at 4 A g–1. The better electrochemical performance of this sample was attributed to the synergistic effect of the Co and V atoms since a minimum amount of V in the structure may distort the crystal lattice and improve the electrolyte diffusion, in addition to the formation of several oxidation states due to reduction of V5+, including V3+ and V4+ as well as to the formation of the metastable V4O9.